(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Carpal Tunnel Syndrome (CTS) is the most common upper extremity compression neuropathy which is a common entrapment neuropathy seen in pregnant women. Objective: The purpose of the present study was to assess presentation and severity of various symptoms among women with CTS in pregnancy and to see the effect of conservative management protocols in alleviation of symptoms of the disease and restoration of functional capability of the affected hands. Methodology: This interventional study was included 36 pregnant women attended in the Outpatient Department of Physical Medicine and Rehabilitation Specialist in the Hi-Tech Multicare Hospital, Dhaka during the period from January 2015 to January 2016 for a period of one year and one month. Detail history was taken and examined physically by a specialist in physical medicine to ascertain the clinical diagnosis. Out of 48 referred cases, 42 pregnant women were identified clinically as CTS cases based on symptoms and signs. However, 2 cases were not enrolled because of severe form of pain and referred to other hospital for admission and 6 patient dropped out. Therefore, 36 cases with CTS symptoms included in this study. All the patients were given conservative treatment (Wrist splint, Exercise and activity modification) for 8 weeks. All patients were followed up at 4 weeks interval. Treatment outcome were measured by Boston carpal tunnel questionnaire (BCTQ). Result: The mean age of the patients is 30±3.5 years. 26 (78%) patients mild to moderate type of CTS symptoms showed improvement in conservative management. Before treatment the mean symptoms severity scale (SSS) of BCTQ) was 2.32±0.4 and for functional status scale (FSS) was it was 1.99±0.43. After treatment for SSS 1.86±0.47 and for FSS 1.53±0.42. And in SSS the p value<.05 and in FSS p value is <.05 which was statistically significant. Conclusion: In conclusion conservative management protocols are sufficient enough in alleviation of symptoms of the disease and is effective for the restoration of functional capability of the affected hand or hands. Journal of National Institute of Neurosciences Bangladesh, 2018;4(2): 101-107